Study on the learning attitudes of biology students to acquire histology knowledge by electronic course in moodle - Necheva, Victoria (Yearbook Telecommunications, 2018)
The present study examines the attitudes of biology students from the Bachelor’s degree programme at the Sofia University "St. Kliment Ohridski" when using Moodle in their course in histology and embryology. Second year students majoring in Biology were studied by questionnaires and narrative interview divided into two types of teaching: the first group of students (with two sub-groups of full-time and part-time students), which in addition to the traditional training in histology also undergo an electronic course in the Moodle platform and the second group students (full-time and part-time students), which are trained in the traditional way. Students in both forms of learning find the Moodle educational environment suitable for histology training. Attitudes to using e-learning among extramural students are higher than those of regular students.